LARVAL DEVELOPMENT OF THE SPIDER CRAB ACANTHONYX-PETIVERII EDWARDS,H.MILNE, 1834 (DECAPODA, MAJIDAE) IN THE LABORATORY - Hiyodo, C. M.; Fransozo, A.; Fransozo, MLN (E J Brill, 1994)
The larval development of Acanthonyx petiverii H. M. Edwards, 1834, was studied in the laboratory through eggs hatched from ovigerous females collected in Ubatuba, state of São Paulo, Brazil. The rearings were carried out in a climatic room with constant temperature (25 degrees +/- 1 degrees C) and salinity (34,5 parts per thousand). The larvae were maintained individually and the food consisted of Artemia nauplii. The larval development of A. petiverii consists of two zoeal stages and a megalopa. All the larval stages were drawn and described in detail. Tables include those presenting morphological characters that allow the identification of zoeae and megalopa of A. petiverii. A comparative study was realized with previously studied majid species that occur in southern and southeastern Brazil.